PEMBUATAN SELAI DARI CAMPURAN BUAH SIRSAK (Annona muricata L.) DENGAN BUAH NAGA MERAH (Hylocereus polyrhizus) - Budiman Budiman; Faizah Hamzah; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to get the good jam from soursop fruit pulp mixing with red dragon fruit pulp. This experiment research used a Completely Randomized Design (CRD) with five treatments as follows: SN1 (soursop fruit pulp 80% : red dragon fruit pulp 20%), SN2 (soursop fruit pulp 65% : red dragon fruit pulp 35%), SN3 (soursop fruit pulp 50% : red dragon fruit pulp 50%), SN4 (soursop fruit pulp 35% : red dragon fruit pulp 65%), SN5 (soursop fruit pulp 20% : red dragon fruit pulp 80%). The result of this research showed that the mixture soursop fruit pulp with red dragon fruit pulp significantly influenced the  moisture content, total dissolved solids, fiber levels, levels of sucrose, the levels of pectin, descriptive tested (colours, aroma, flavor, and texture), hedonic tested (taste, texture and overall), but did not significantly affect the ash content, hedonic tested (colours and aroma). The treatmen SN1 (soursop fruit pulp 80% : 20% red dragon fruit pulp) produced a better jam. This jam had moisture content 21.40%, fiber level 3.59%, sucrose level 60.05%, pectin level 0.69% and hedonic tested liked by the panelists and descriptive test colours, aroma, sweetness and creamy texture more dominant. Keywords: jam, soursop fruit, red dragon fruit and mixing pureed fruit.